Antagonistic studies and hyphal interactions of the new antagonist Aspergillus piperis against some phytopathogenic fungi in vitro in comparison with Trichoderma harzianum. (December 2017) - El-Debaiky, Samah A.
Abstract: The present study represents, for the first time, the detailed studies about the hyphal interactions of Aspergillus piperis, as a new antagonist, against some isolated plant pathogenic fungi ( Alternaria alternata, Alternaria solani, Botrytis cinerea, Sclerotium cepivorum and Sclerotinia sclerotiorum ) in vitro. The bio-controlling capability of A. piperis against the tested phytopathogens was tested using the dual culture method. This experiment revealed that A. piperis had antagonistic activity and reduced the growth of the tested phytopathogens and grew over their mycelia in the paired plates. Also, several antagonistic mechanisms were recorded, in this study, between A. piperis and the tested phytopathogens using the microscopic examination. The bio-controlling activity and the antagonistic mechanisms exhibited by the new antagonist, A. piperis were compared with those obtained by the common antagonist, Trichoderma harzianum against the same phytopathogens. The obtained results showed that, A. piperis was more effective than T. harzianum in inhibiting all the tested species in the dual culture plates. The best result was 81.85% inhibition percentage against S. sclerotiorum by A. piperis while, T. harzianum exhibits only 45.18%. Moreover, several antagonistic mechanisms and hyphal interactions were investigated among the hyphae of both A.piperis and T. harzianum and the hyphae of the tested phytopathogens. These mechanisms were summarized as; mycoparasitism (coiling and penetration of the hyphae) and antibiosis in the form of lysis of the hyphal cells and spores, denaturation and breaking of the hyphae. The indirect interaction (antibiosis) and the direct mycoparasitism were observed by A. piperis against all the tested phytopathogens, but it attacked the hyphae and conidiophores of A. alternata by only the antibiosis interaction. The microscopic examination revealed also that T. harzianum attacked the tested phytopathogens by both antibiosis and mycoparasitism except against A. solani which attacked only by mycoparasitism. Highlights: Some phytopathogenic fungi were isolated from spoiled tomatoes, onions and strawberry then identified morphologically. The new antagonist, Aspergillus piperis, suppressed the growth of the isolated phytopathogenic fungi. Several hyphal interactions between the hyphae of A. piperis and the phytopathogens were examined microscopically and summarized as; mycoparasitism and antibiosis. The antagonistic activity and hyphal interactions of A. piperis against the phytopathogens were compared to Trichoderma harzianum. A. piperis was more effective.